Endometriosis and preterm birth: A Danish cohort study - Kjerstine Breintoft; Linn Håkonsen Arendt; Niels Uldbjerg; Maria Tølbøll Glavind; Axel Forman; Tine Brink Henriksen (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Emerging evidence shows that women with endometriosis face a higher risk of preterm birth. However, the pathways are unclear. The objective of this study is to further investigate at different gestational ages the association between endometriosis and different pathways of preterm birth including, medically indicated preterm birth, premature pre‐labor rupture of membranes (PPROM), and spontaneous labor contractions. Material and methods In this population‐based cohort study we linked singleton pregnancies from the Aarhus Birth Cohort to the Danish National Patient Registry, the Danish Medical Birth Registry, the Danish National Pathology Registry and Data Bank, and the Danish in vitro fertilization registry to gather information on endometriosis status, outcomes and maternal characteristics. We investigated preterm birth before 37 completed weeks of gestation and very preterm birth before 32 completed weeks of gestation. We explored different pathways including medically indicated preterm birth defined as induction of labor with intact membranes and no prior labor contractions, PPROM defined as rupture of membranes, and spontaneous labor contractions defined as contractions with intact membranes resulting in labor. Results We found that women with endometriosis had an increased risk of preterm birth before 37 gestational weeks overall (adjusted hazard rate [aHR] 1.6, 95% confidence interval [CI] 1.3–1.9) and very preterm birth before 32 gestational weeks (aHR 1.8, 95% CI 1.1–2.9) compared with women without endometriosis. Medically indicated preterm birth was more prominent in women with endometriosis in deliveries before 37 gestational weeks (aHR 2.4, 95% CI 1.8–3.2) whereas spontaneous labor contractions were more common before 32 gestational weeks (aHR 2.2, 95% CI 1.1–4.5) in women with endometriosis compared with women without endometriosis. Further, in the analyses restricted to women with a histologically verified diagnosis of endometriosis, the results were strengthened overall and showed that women with endometriosis had an increased risk of PPROM before 32 gestational weeks (aHR 3.49, 95% CI1.36–8.98). Conclusions Endometriosis was associated with both preterm and very preterm birth; however, apparently through different pathways. Women with endometriosis were more prone to have medically indicated preterm births before 37 gestational weeks and spontaneous preterm births before 32 gestational weeks compared with women without endometriosis.